Trust in Contemporary Society - Sasaki, Masamichi (International comparative social studies, 2019)
Trust in Contemporary Society, by well-known trust researchers, deals with conceptual, theoretical and social interaction analyses, historical data on societies, national surveys or cross-national comparative studies, and methodological issues related to trust. The authors are from a variety of disciplines: psychology, sociology, political science, organizational studies, history, and philosophy, and from Britain, the United States, the Czech Republic, the Netherlands, Australia, Germany, and Japan. They bring their vast knowledge from different historical and cultural backgrounds to illuminate contemporary issues of trust and distrust. The socio-cultural perspective of trust is important and increasingly acknowledged as central to trust research. Accordingly, future directions for comparative trust research are also discussed. Contributors include: Jack Barbalet, John Brehm, Geoffrey Hosking, Robert Marsh, Barbara A. Misztal, Guido Möllering, Bart Nooteboom, Ken J. Rotenberg, Jiří Šafr, Masamichi Sasaki, Meg Savel, Markéta Sedláčková, Jörg Sydow, Piotr Sztompka.